2002
DOI: 10.1038/sj.bjp.0704588
|View full text |Cite
|
Sign up to set email alerts
|

The human 5‐HT7 serotonin receptor splice variants: constitutive activity and inverse agonist effects

Abstract: 1 Using membranes from stably or transiently transfected HEK293 cells cultured in 5-HT-free medium and expressing the recombinant human 5-HT 7 receptor splice variants (h5-HT 7(a) , h5-HT 7(b) and h5-HT 7(d) ), we compared their abilities to constitutively activate adenylyl cyclase (AC). 2 All h5-HT 7 splice variants elevated basal and forskolin-stimulated AC. The basal AC activity was reduced by the 5-HT 7 antagonist methiothepin and this e ect was blocked by mesulergine (neutral 5-HT 7 antagonist) indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 34 publications
4
98
1
Order By: Relevance
“…It has been reported that several 5-HT receptors possess a constitutive, agonist-independent activity (Krobert and Levy, 2002). In the case of the 5-HT 7 receptor, we found that increased levels of 5-HT 7 cDNA (from 20 to 400 ng) resulted in a significant increase of SRE activity (from twofold to fivefold) under nonstimulated conditions (Fig.…”
Section: Resultssupporting
confidence: 58%
“…It has been reported that several 5-HT receptors possess a constitutive, agonist-independent activity (Krobert and Levy, 2002). In the case of the 5-HT 7 receptor, we found that increased levels of 5-HT 7 cDNA (from 20 to 400 ng) resulted in a significant increase of SRE activity (from twofold to fivefold) under nonstimulated conditions (Fig.…”
Section: Resultssupporting
confidence: 58%
“…One of the characteristic features of 5-HT7 receptor is a high constitutive basal activity and results in homologous desensitization. Correspondingly, 5-HT7 receptors can be resensitized by a short exposure to antagonist, also known as reverse agonists, such as metergoline (MG) (24,25). We used this characteristic behavior of 5-HT7 to confirm that responses of mammary epithelial cells to 5-HT were consistent with these known properties of 5-HT7.…”
Section: Transmembrane Conductance Is Regulated By the 5-ht7mentioning
confidence: 90%
“…Levy's group also extensively characterized the ability of the three isoforms to constitutively activate adenylyl cyclase and the inverse agonist properties of a series of antagonists. Again, 5-HT 7(a) , , and 5-HT 7(d) displayed similar profiles for both constitutive activity and inverse agonist responses (Krobert and Levy, 2002).…”
mentioning
confidence: 79%